2017
DOI: 10.1002/jcp.26069
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin stimluates apoptosis by inducing generation of ROS and ER stress in human choriocarcinoma cells

Abstract: Silibinin is a flavonolignan extracted from seeds of milk thistles. Traditionally, it has been used as a therapeutic agent for liver disorders, and now it is well-known for its anti-cancer effects. However, studies on anti-cancer effects of silibinin on choriocarcinoma are very limited. Therefore, we performed proliferation and apoptosis assays to determine effects of silibinin on the viability of human choriocarcinoma (JAR and JEG3) cells. Our results showed that silibinin significantly inhibited proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 37 publications
(42 reference statements)
2
12
0
Order By: Relevance
“…Following induction of GRP78, ER stress signals lead to activation of ATF4/CHOP, which has been reported to sensitize cells to apoptosis [33]. Similar to the above results, silibinin-induced ER stress-dependent apoptosis in choriocarcinoma cells is closely related to the GRP78 signaling pathways [34]. It has also been reported that CHOP, the ER stress-induced transcription factor, not only down-regulates Bcl-2 expression, but also leads to translocation of Bax from the cytosol to the mitochondria [35].…”
Section: Discussionsupporting
confidence: 72%
“…Following induction of GRP78, ER stress signals lead to activation of ATF4/CHOP, which has been reported to sensitize cells to apoptosis [33]. Similar to the above results, silibinin-induced ER stress-dependent apoptosis in choriocarcinoma cells is closely related to the GRP78 signaling pathways [34]. It has also been reported that CHOP, the ER stress-induced transcription factor, not only down-regulates Bcl-2 expression, but also leads to translocation of Bax from the cytosol to the mitochondria [35].…”
Section: Discussionsupporting
confidence: 72%
“…Li et al (2017) showed that silibinin induced apoptosis in gastric cancer BGC823 cells [ 32 ]. Silibinin induced apoptosis in human choriocarcinoma cells [ 33 ]. The anti-cancer effects of SLM and silibinin on salivary gland cancer have also been reported by Choi et al (2017) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Silibinin, the most famous and active compound isolated from Silybum marianum (milk thistle) traditionally used to protect from liver injury, could induce apoptosis related to mitochondrial Ca 2+ influx in C. albicans cells [ 84 , 85 ]. Silibinin could alleviate mitochondrial dysfunction in mice model of cisplatin-induced acute kidney injury through Sirt3 activation, although in vitro proapoptotic effects through inducing ROS production have been also reported [ 86 , 87 ]. The safe profile with silibinin, evidenced by marketed health food and clinical trials, makes silibinin a very promising candidate for antifungal therapies against Candida infections although there is still a long way to go [ 88 ].…”
Section: Compounds Targeting Mitochondriamentioning
confidence: 99%